IMPLEMENTASI KURIKULUM MERDEKA DALAM PENDIDIKAN SENI: STUDI KASUS DI SEKOLAH DASAR - Regina, Belinda Dewi; Hartono; Eko Raharjo (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to describe and analyze the implementation of the Independent Curriculum in arts education at the elementary school level. The Independent Curriculum, which emphasizes differentiated learning, strengthening the profile of Pancasila students, and teacher freedom in designing learning, is the main framework in the transformation of arts education. This study uses a qualitative approach with a case study method in one of the elementary schools that has implemented the Independent Curriculum. Data collection techniques were carried out through observation, in-depth interviews with art teachers, principals, and documentation of arts learning activities. The results of the study show that the implementation of the Independent Curriculum in arts education provides more space for students to express themselves and be creative according to their potential and interests. Arts learning becomes more contextual and enjoyable, with the integration of local cultural themes and the use of varied media. However, several obstacles were also found, such as limited resources, teacher readiness, and uneven understanding of the principles of the Independent Curriculum. This study recommends the need for intensive training for art teachers and the development of local culture-based learning modules to support the optimal implementation of the Independent Curriculum in the field of arts education.